Banana Stem Fiber Potential as an Alternative Natural Geosynthetic Material for Soil Reinforcement and Protection - Bartholomeus, Bartholomeus; Purba, Luki Hariando; S P Manurung, Charles; Sihombing, Wanto Poller (Rekayasa Sipil, 2025)
Geosynthetics for soil reinforcement and protection require tensile strength and the ability to absorb water. Based on previous studies, it was found that banana stem fibers have both of these mechanical properties of geosynthetics. However, these two strong mechanical properties are not enough for geosynthetic applications. Several other mechanical properties are needed. Therefore, geosynthetic samples were made using spun and woven banana stem fiber materials in this study. The spun was made with different diameters, namely 5 mm, 7.5 mm, and 10 mm, and woven like a mat for one direction of tensile force. Then, additional tests were carried out in addition to tensile strength and water absorption, such as tear strength, puncture strength, and permeability based on permittivity. From the test results, only the woven fabric with a 5 mm spun diameter meets all requirements except for its permittivity value, where the average tensile strength, average tear strength, and average puncture strength obtained for elongation <50% are 32.0 kN/m, 628.7 N, and 1915.8 N, respectively. At the same time, the average water absorption for all diameter variations is 408.07% to 441.86%. So banana stem fibers, especially those with a 5 mm spun diameter, have the potential as an alternative natural geosynthetic material for soil reinforcement and protection by considering the spun fiber woven pattern to improve the permittivity.